Land policies, tourism projects, and tourism development in Guangdong. Issue 2 (3rd April 2017) - Xu, Honggang; Xiang, Zhenying; Huang, Xingyu
ABSTRACT: The dual-track land system is a key underlying reason for many phenomena in transitional China, and land acquisition is often based on the bargaining process among government agencies, businesses and landowners. As a growing new economic sector, tourism is in a less advantageous position in obtaining land from governments, and land is often regarded as one of the constraints for tourism development. This study attempts to illustrate how the tourism sector makes efforts to obtain land for development from provincial governments, with a focus on the case of the Guangdong province. It was found that lobbying the provincial government and other sectors to formulate tourism land policies and packaging big projects to be included in provincial government priority projects are the two means to obtain land for tourism. However, in this process, obtaining land rather than ensuring the sustainable use of land tends to have been the focus. Suggestions are provided at the end of this paper.